The potential and emerging role of quantitative imaging biomarkers for cancer characterization - Tharmaseelan, Hishan; Hertel, Alexander; Singer, Shereen; Nörenberg, Dominik; Haselmann, Verena; Schönberg, Stefan; Froelich, Matthias F. (Cancers, 2022)
Similar to the transformation towards personalized oncology treatment, emerging techniques for evaluating oncologic imaging are fostering a transition from traditional response assessment towards more comprehensive cancer characterization via imaging. This development can be seen as key to the achievement of truly personalized and optimized cancer diagnosis and treatment. This review gives a methodological introduction for clinicians interested in the potential of quantitative imaging biomarkers, treating of radiomics models, texture visualization, convolutional neural networks and automated segmentation, in particular. Based on an introduction to these methods, clinical evidence for the corresponding imaging biomarkers—(i) dignity and etiology assessment; (ii) tumoral heterogeneity; (iii) aggressiveness and response; and (iv) targeting for biopsy and therapy—is summarized. Further requirements for the clinical implementation of these imaging biomarkers and the synergistic potential of personalized molecular cancer diagnostics and liquid profiling are discussed.
Dieser Artikel gehört zur Collection: Imaging biomarker in oncology
Gesehen am 19.12.2023